Hành vi chấp nhận sử dụng ngân hàng số: Sự khác biệt giữa khu vực Thành phố Hồ Chí Minh và Đồng bằng Sông Cửu Long - Nguyễn Quốc, Anh; Tăng Mỹ, Sang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
To narrow the gap in accessing digital banking services between urban and rural areas, the study was conducted to find out the differences in factors affecting the behavior of accepting digital banking services based on demographic characteristics. The research model includes four variables: Perceived usefulness, perceived ease of use, perceived safety, and consumer behavior. Research data is surveyed from 1.172 people who have been using e-banking services in two areas of Ho Chi Minh City and the Mekong Delta, these are two areas with different levels of access to digital banking services. To process data, the article uses linear structural analysis (SEM) and SmartPLS 3.0 software. Research results show that there is a difference in perceived ease of use between these two regions although the difference is not large. There are also differences in the impact of perceived safety on the consumption behavior of people in these two regions. Based on the research results, the article proposes implications for solutions to promote the acceptance behavior of digital banking users.
Keywords: Consumer behavior; Digital banking; TAM model; Difference